KONTRIBUSI USAHATANI PADI SAWAH TERHADAP PENDAPATAN USAHATANI KELUARGA DI DESA OGOAMAS II KECAMATAN SOJOL UTARA KABUPATEN DONGGALA - Anton M, Marhawati, Gapri (AGROTEKBIS, 2016)
The purpose of this study was to  know how much Contributions farming  rice on Family Farm income in the village Ogoamas II  District North Sojol Donggala.  The research was conducted in January until March 2014. The determination of the respondents was conducted using a random sample (simple random sampling), with consideration of the number of respondents who were taken in the study of 30 farmers. The analysis used in this study is analysis income. The study results showed that the average/ha income received by farmers for rice fields where the average income of  Rp. 21,354,507.27. Corn farming an average income of Rp 3,959,324.95. Peanut farming an average of  income Rp.13,485,193.66. Cocoa farming, an average income of Rp. 1,819,418.92. Coconut Copra farming an average income of  Rp.3,707,.395.60. The amount of revenue contribution rice farming to farming families, reaching 48,18%, while the revenue contribution  8,94% of farm corn, peanut farming 30,43%, and  4,11%, cocoa farming, and farming coconut copra 8,37%. Rice farming provided the largest contribution compared to other farming.